"Gros populas". La Boétie as symptomatic misunderstanding - Cappelli, Guido (Res Publica. Revista de Historia de las Ideas Políticas, 2019)
With its rhetorical impetus, with its allure of singing for freedom, the brilliant and successful Discours de la servitude volontaire by Étienne de la Boétie (XVIth century) has fascinated several generations of intellectuals, to the point of becoming, bon gré mal gré, the perfect alibi for justifying a system such as the political liberalism of our time–it doesn’t matter if “progressive” or reactionary–, which is presented as “democratic”, whereas, as a matter of fact, it is grounded on the prevailance of political and economic elites that control an indistinct and diffuse ‘middle class’ that increasingly resembles the dangerous “populace” evoked in the pamphlet. This essay seeks to review the critical literature on De la Boétie’s work by proposing an interpretation that links it to the previous political doctrine and, at the same time, to the historical climate of the contemporary French Monarchy. The contradictions of the text are thus highlighted: while it seems to defend the ideas of individual freedom and political equality, it conceals reasons –of deep oligarchic roots– that point to the defence of class and distrust towards the nascent modern State, based on popular consensus and centralized bureaucracy, and represented, using Gramsci’s terms, by the French Monarchy in the process of definitive consolidation and affirmation.
Keywords: La Boétie; Political thought; People; France; XVIth Century.